The Effect of Digital Marketing Strategy on Increasing Sales at PT Jakarta Energi Logistik - Metya Lutviani; Ihsanul Haqqi (ASIAN PUBLISHER, 2023)
This research has the title Effect of Digital Marketing Strategy on Increasing Sales at PT Jakarta Energi Logistik. The research was conducted because digital marketing has shown very fast growth in the Covid 19 era. The growth in the sales value of online businesses in Indonesia is increasing every year. The problem in this study focuses on whether the digital marketing strategy has an effect on increasing sales at PT Jakarta Energi Logistik and how much influence the digital marketing strategy has on increasing sales at PT Jakarta Energi Logistik. This study aims to examine and analyze the influence of digital marketing strategies and increased sales of PT Jakarta Energi Logistik. The research method uses descriptive quantitative, data collection techniques through questionnaires. The population and research sample are 30 respondents, the sampling method uses saturated sampling. The results of this study indicate that the digital marketing strategy variable has a significant effect on increasing sales at PT Jakarta Energi Logistik. There are as many as 62.3% influenced by social media on sales volume.